Perhitungan Peramalan Dan Penyimpangan Dari Data Penjualan Lampu PT.Cahaya Cemerlang Abadi Datan Penjualan Tahun 1994-1998 - Siti Elza Tania Elvira Titania; Aufa Mishbah; Haikal Mahadi; Hafish Alfarizy (Jurnal Teknik Mesin Unsyiah, 2021)
The problem commonly faced by companies is how to predict future production of goods based on previously recorded data. the company only produces according to orders, so the company only carries out the production process according to the quantity demanded by consumers, if there is an excess in production, the excess will be stored in stock, this is to meet sudden consumer demand. The purpose of this study is to identify and analyze the results of forecasting light bulb production using the Moving Average and Exponential Smoothing forecasting methods.